Financial education in schools: A meta-analysis of experimental studies. (October 2020) - Kaiser, Tim; Menkhoff, Lukas
Abstract: We study the literature on school financial education programs for children and youth via a quantitative meta-analysis of 37 (quasi-) experiments. We find that financial education treatments have, on average, sizeable impacts on financial knowledge (+0.33 SD), similar to educational interventions in other domains. Additionally, we document smaller effects on financial behaviors among students (+0.07 SD). When restricting the sample to 18 randomized experiments average effect sizes are estimated to be about 0.15 SD units on financial knowledge and 0.07 SD units on financial behaviors. These results are robust irrespective of the meta-analytic method used and when accounting for publication bias. Subgroup analyses show the beneficial effect of more intensive treatments, albeit with decreasing marginal returns.